An Explanatory Sequential Mixed-Methods Evaluation of Consecutive Dry Day Information Dissemination for Forest and Land Fire Disaster Risk Reduction in West Kotawaringin - Nur Setiawan; Yohana N Maharani; Johan Danu Prasetya; Tedy Agung Cahyadi; Eko Teguh Paripurno (Journal of Applied Geospatial Information, 2026)
Forest and land fires frequently occur in Indonesian tropical peatlands due to prolonged dry periods. Although the Indonesian Meteorology, Climatology, and Geophysics Agency (BMKG) routinely disseminates consecutive dry day (HTH) information, its effectiveness in supporting forest and land fire prevention has received limited attention. This study evaluated the relationship between HTH and hotspot occurrence and assessed the effectiveness of HTH information dissemination using an explanatory sequential mixed-methods approach. Pearson correlation analysis was applied to HTH and hotspot data collected during 2023-2024, while stakeholder perceptions were evaluated through questionnaires involving 43 respondents and supported by semi-structured interviews. The results revealed a positive relationship between HTH and hotspot occurrence, with a stronger correlation during the 2023 El Niño period than in 2024. Stakeholders showed a very high perception of HTH information dissemination, with an overall mean score of 4.239 and excellent questionnaire reliability (Cronbach's α = 0.9862). However, qualitative findings indicated that institutional coordination and differences in technical understanding affected the operational use of HTH information. These findings demonstrate that effective forest and land fire early warning systems require not only reliable climate indicators but also effective dissemination and institutional coordination to support timely mitigation. Overall, this study demonstrates that HTH-based consecutive dry day information dissemination constitutes an integral component of a science-based Disaster Risk Reduction (DRR) and Disaster Management strategy, bridging meteorological monitoring with multi-stakeholder preventive action in tropical peatland fire-prone regions.